EPR Study of Coffee - S, Munkhtsetseg; M, Turbold; G, Shilagardi (Scientific transaction of the National University of Mongolia. Physics, 2022)
Six medium and dark roast coffees and its grounds and one non-roast coffee samples in solid state from the one of coffee shops in Ulaanbaatar city were studied by the EPR spectroscopy. Singlet, low intensity but broad (16-17 Gs) EPR spectrum was registered near the 3400 Gs magnetic field from the all samples. Free radical concentration was evaluated about 1016 spin which can be a measure of antioxidative property.